“A novel by an English governess”: How I.I. Vvedensky’s translation altered Ch. Brontë’s novel Jane Eyre - E. I. Samorodnitskaya (Шаги)
Even though the Russian reception of Ch. Brontë’s novel Jane Eyre, as well as I.I. Vvedensky’s translation activity, have been the object of research more than once, a systematic analysis of the 1849 translation in the context of Russian reception of the Victorian novel has not yet become the subject of special study. The article attempts to analyze the “liberties” in the translation of the novel, which include both domestication, characteristic for its time, and omissions of passages that contain religious motifs. The author of the article suggests that such omissions may be due to both extra-literary factors, in particular, an indirect ban on mentioning Western Christianity of any confession, in any context, and the emerging literary paradigm of the “progressive” realistic novel, for which religious issues are irrelevant. Vvedensky’s translation in 1849 set the frame for perception of Brontë’s novel, which retained the plot, action, attention to the narrated story and the unique heroine. The philosophical-religious, anti-ideological problems raised in the novel faded into the background or were entirely neutralized. This is a watered down novel by Ch. Brontë; yet even in such an abbreviated version it made an impression on the reader both in the 19th and in the 20th centuries, because omissions of religious matters, albeit for other ideological reasons, are preserved in V.O. Stanevich’s translation made in the Soviet period (1950).